Numerical experiments on the determination of stress concentration factors in orthotropic perforated plates subjected to in plane loading - Bambill, Diana Virginia (2009)
As it is known, laminated composite materials are increasingly used in many technological applications, and in some instance, cutouts must be made into laminated panels for practical reasons, changing the stress distribution. The present study deals with the determination of the stress concentration factor that holes of square shape cause in an orthotropic plate subjected to distributed in plane loading. Square holes of rounded corners in a rectangular plate are considered, and the effect of different combinations of axial and tangential forces applied to its middle plane at the external edges, is studied. The mutually perpendicular axes, which define the principal axes of orthotropy, are assumed in many different directions referred to the sides of the plate. Numerical experiments by means of a finite element code is performed, evaluating the influence of the fiber orientation with respect to the edges of the plate and the characteristics of the orthotropic materials since such structures do not exhibit easily predictable behavior.